2017
DOI: 10.1007/s11701-017-0674-4
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of cost and operative outcomes of robotic hysterectomy compared to laparoscopic hysterectomy across different uterine weights

Abstract: Operative cost and outcomes between robotic and laparoscopic hysterectomy across different uterine weights. Retrospective cohort study including patients undergoing robotic and laparoscopic hysterectomy for benign disease at an Academic university hospital. One hundred and ninety six hysterectomies were identified (101 robotic versus 95 laparoscopic). Demographic and surgical characteristics were statistically equivalent. Robotic group had a higher body mass index (±SD) (32.9 ± 6.5 versus 30.4 ± 7.1, p 0.012) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
24
1
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 31 publications
(28 citation statements)
references
References 20 publications
2
24
1
1
Order By: Relevance
“…It is known that robotic technology is substantially costlier, which is a real concern, considering the increasing pressure to contain costs moving forward. Nevertheless, there is limited evidence of cost analysis studies comparing robotic to laparoscopic hysterectomy for benign indications [1621] and just 6 studies including abdominal or vaginal approaches [2227]. Most of those authors conclude that robotic surgical technology appears to be safe and feasible with similar clinical outcomes to open and laparoscopic surgery, and although the clinical evidence of effectiveness is poor, RAH costs are consistently higher than the cost of CLH.…”
Section: Discussionmentioning
confidence: 99%
“…It is known that robotic technology is substantially costlier, which is a real concern, considering the increasing pressure to contain costs moving forward. Nevertheless, there is limited evidence of cost analysis studies comparing robotic to laparoscopic hysterectomy for benign indications [1621] and just 6 studies including abdominal or vaginal approaches [2227]. Most of those authors conclude that robotic surgical technology appears to be safe and feasible with similar clinical outcomes to open and laparoscopic surgery, and although the clinical evidence of effectiveness is poor, RAH costs are consistently higher than the cost of CLH.…”
Section: Discussionmentioning
confidence: 99%
“…Also, although outpatient robotic hysterectomy was demonstrated to be safe and associated with financial savings ( 32 , 33 , 34 ), its safety and feasibility has not yet been evaluated in the obese patient subset. Similarly, costs of robotic gynecologic surgery in benign cases were analyzed with strategies for efficiency ( 35 , 36 ), but there is paucity of the effect of BMI on cost in benign robotic hysterectomy. In addition, because the incidence of occult cancer discovered after minimally invasive gynecologic surgery has been examined ( 37 ), there is a need to examine it in the obese patient population.…”
Section: Discussionmentioning
confidence: 99%
“…For this reason, they suggested that such patients may benefit from preoperative measures to facilitate earlier discharge [27]. Moreover, Moawad et al showed that robotic hysterectomy for uteri weighing more than 750 gr is associated with shorter mean operative time and improved cost profile compared to laparoscopic approach [28]. Not enough data could be found regarding the possible need of additional postoperative cancer therapies and equivalent cancer specific and overall survival compared to other approaches.…”
Section: Discussionmentioning
confidence: 99%